The professionalism disconnect: do entering residents identify yet participate in unprofessional behaviors? - Nagler, Alisa (BioMed Central, 2014)
BACKGROUND: Professionalism has been an important tenet of medical education, yet defining it is a challenge. Perceptions of professional behavior may vary by individual, medical specialty, demographic group and institution. Understanding these differences should help institutions better clarify professionalism expectations and provide standards with which to evaluate resident behavior. METHODS: Duke University Hospital and Vidant Medical Center/East Carolina University surveyed entering PGY1 residents. Residents were queried on two issues: their perception of the professionalism of 46 specific behaviors related to training and patient care; and their own participation in those specified behaviors. The study reports data analyses for gender and institution based upon survey results in 2009 and 2010. The study received approval by the Institutional Review Boards of both institutions. RESULTS: 76% (375) of 495 PGY1 residents surveyed in 2009 and 2010 responded. A majority of responders rated all 46 specified behaviors as unprofessional, and a majority had either observed or participated in each behavior. For all 46 behaviors, a greater percentage of women rated the behaviors as unprofessional. Men were more likely than women to have participated in behaviors. There were several significant differences in both the perceptions of specified behaviors and in self-reported observation of and/or involvement in those behaviors between institutions. Respondents indicated the most important professionalism issues relevant to medical practice include: respect for colleagues/patients, relationships with pharmaceutical companies, balancing home/work life, and admitting mistakes. They reported that professionalism can best be assessed by peers, patients, observation of non-medical work and timeliness/detail of paperwork. CONCLUSION: Defining professionalism in measurable terms is a challenge yet critical in order for it to be taught and assessed. Recognition of the differences by gender and institution should allow for tailored teaching and assessment of professionalism so that it is most meaningful. A shared understanding of what constitutes professional behavior is an important first step.